SEISMIC RESISTANCE IN THE CORE OF CARAL, PERU - Vargas-Neumann, Julio; Iwaki, Carlos; Rubiños, Álvaro (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The great antiquity of the city of Caral and the level of engineering found in the pyramids leads to the conclusion that its construction technologies inluenced the development of the ceremonial architecture of Peru and America. A irst realization is that the pyramids were structurally secure due to the stability of their nuclei. The pyramids were stable as stepped platforms, resulting from the burial of previous structures, which was the religious and spiritual conception associated with the structural design. These buildings were treated as living beings that wanted to immortalize themselves with their deities, and once their stage of life came to an end, it was buried to generate yet a gerater stepped-pyramid structure. Burials of the pyramids were carried out with speciic materials and technologies developed to achieve the overall stability of the pyramid against seismic events. Platform nuclei were formed through trial and error, with materials of increasing internal friction and greater percentage of voids (angular stones), aimed to incerase lateral stability. The greatest revelation was the use of tension reinforcements. Builders invented bags of vegetal iber containing stones in a stable equilibrium, which produced a strong earthquake resistant behavior in the cores of the pyramids. These were the forerunners of today’s gabion technology. The façades of stone and earth were, for aesthetic purposes, plastered and decorated. They were the mutable skin of the immortal structure. Additionally, in Caral, the technology of wood, cane, vegetal ibers and earth was developed, known as quincha, which was later re-used in the colonial architecture of Lima, as an earthquake resistant solution following the catastrophic earthquakes of 1687 and 1746. This paper is presented by the structural group of Caral, part of an interdisciplinary team, which describes the details of the research carried out at the pyramid called ‘La Galería’, where signiicant progress in earthquake resistant engineering has been ascertained, developed in Peru over 5,000 years ago.